2023
DOI: 10.1001/jamanetworkopen.2023.1055
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intensive vs Standard Blood Pressure Control With Regional Changes in Cerebral Small Vessel Disease Biomarkers

Abstract: ImportanceLittle is known about the associations of strict blood pressure (BP) control with microstructural changes in small vessel disease markers.ObjectiveTo investigate the regional associations of intensive vs standard BP control with small vessel disease biomarkers, such as white matter lesions (WMLs), fractional anisotropy (FA), mean diffusivity (MD), and cerebral blood flow (CBF).Design, Setting, and ParticipantsThe Systolic Blood Pressure Intervention Trial (SPRINT) is a multicenter randomized clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…Previous literature has established the contributions of high blood pressure and hypertension 223 , 224 to cSVD. However, studies using antihypertensive medications targeting reductions in cSVD have been sparse 8 and demonstrate overall mixed responses, 225 , 226 , 227 , 228 suggesting that additional contributing factors may interact with or independent of hypertension and other traditional comorbidities. In line with the present study's findings, a recent series of randomized controlled trials, LACI‐1 and LACI‐2 (Lacunar Intervention Trial‐1 and Trial‐2), demonstrated that treatments targeting vascular endothelial function improved cerebrovascular reactivity in patients with cSVD 229 and improved their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has established the contributions of high blood pressure and hypertension 223 , 224 to cSVD. However, studies using antihypertensive medications targeting reductions in cSVD have been sparse 8 and demonstrate overall mixed responses, 225 , 226 , 227 , 228 suggesting that additional contributing factors may interact with or independent of hypertension and other traditional comorbidities. In line with the present study's findings, a recent series of randomized controlled trials, LACI‐1 and LACI‐2 (Lacunar Intervention Trial‐1 and Trial‐2), demonstrated that treatments targeting vascular endothelial function improved cerebrovascular reactivity in patients with cSVD 229 and improved their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…161 Intriguingly, intensive BP-lowering regimens may offer increased benefit relative to standard therapy. Recent findings from secondary analyses of the SPRINT-MIND data set indicate diminished risk of cognitive decline, 10,95 WML development, 162 and probable dementia 9 in patients undergoing intensive blood-pressure-lowering (SBP <120 mm Hg). Intensive regimens, but not standard, were also found to ameliorate cognitive decline in patients with high BPV.…”
Section: Role For Antihypertensive Therapy?mentioning
confidence: 99%
“…Korrespondierend kann gezeigt werden, dass eine intensive Senkung des systolischen Blutdrucks auf Werte < 120 mmHg das Demenzrisiko reduziert und eine Progression der zerebralen Mikroangiopathie verlangsamt [16,17].…”
Section: Die Mittlere Lebensphaseunclassified